Improving the Professionalism of Elementary School Teachers by Using a Collaborative Academic Supervision Model - Sholihah, Barid; Marmoah, Sri; Roemintoyo, Roemintoyo (Universitas Sebelas Maret, 2026)
This study aims to improve the professionalism of elementary school teachers through the application of a collaborative academic supervision model. This study is a School Action Research (SAR) conducted at SDN 01 Delingan with 7 teachers as research subjects. The study was conducted in two cycles, each of which included the stages of planning, implementation of actions, observation, and reflection. Data collection techniques used observation, interviews, and documentation. Data were analyzed descriptively, qualitatively, and quantitatively.The results showed that the implementation of collaborative academic supervision could significantly improve teacher professionalism. The average teacher professionalism score at the beginning of the study was 62.25, increasing to 72.25 in cycle I and further increasing to 85.25 in cycle II. The improvement occurred in the aspects of lesson planning, lesson implementation, use of methods and media, and lesson evaluation. Collaborative academic supervision encourages active teacher involvement, improves learning reflection, and creates a partnership between the principal and teachers. Based on these results, it can be concluded that the collaborative academic supervision model is effective as an effort to improve the professionalism of elementary school teachers and can be used as an alternative academic supervision strategy in schools.